Neuronal RNA processing: cross-talk between transcriptional regulation and RNA-binding proteins - Ozbulut, Hasan Can; Hilgers, Valérie (Frontiers in Molecular Neuroscience, 2024)
In the nervous system, alternative RNA processing is particularly prevalent, which results in the expression of thousands of transcript variants found in no other tissue. Neuron-specific RNA-binding proteins co-transcriptionally regulate alternative splicing, alternative polyadenylation, and RNA editing, thereby shaping the RNA identity of nervous system cells. Recent evidence suggests that interactions between RNA-binding proteins and cis-regulatory elements such as promoters and enhancers play a role in the determination of neuron-specific expression profiles. Here, we discuss possible mechanisms through which transcription and RNA processing cross-talk to generate the uniquely complex neuronal transcriptome, with a focus on alternative 3′-end formation.